Science and public policy the virtuous corruption of virtual environmental science - Kellow, Aynsley J. (Aynsley John), 1951-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2007)
This book is an examination of a neglected form of scientific corruption--corruption by political attachment to noble causes.
1. The political ecology of Pseudonovibos spiralis and the virtuous corruption of virtual science -- 2. The political ecology of conservation biology -- 3. Climate science as 'post-normal' science -- 4. Defending the litany : the attack on the skeptical environmentalist -- 5. Sound science and political science -- 6. Science and its social and political context.
Includes bibliographical references and index.
Keywords: Environmental policy; Precautionary principle; Science and state; Corruption; Electronic books